“My favourite mask is myself”: camuffamenti, amplificazioni e straniamenti nella recitazione di Orson Welles - Mariapaola Pierini (Between, 2019)
In the extensive bibliography devoted to Orson Welles, his intense and crucial activity as an actor has been seldom investigated. Welles himself has always eluded the issue, considering his acting too tied to his "cumbersome personality". Nonetheless, his long acting career is not only relevant in itself, but appears to work as a mirror, at times distorted, of his role as a director and as a public figure. Furthermore, his performances are linked by a recognizable expressive strategy, marked by an irrepressible drive towards masquerade and falsification of his own physical features. This impulse, which is inseparable from the modernity of his work, culminates in an emblematic film, F for Fake (1973). This article aims to shed light on Welles as an actor, starting from archive materials and through an overview of his entire career. The purpose is to look at his performances in the light of the different strategies of mutation of his own real appearance (amplification, aging, degradation, camouflage), in relation to the different contexts and to the physiological changes occurring in his body. The article therefore presents a chronological overview and a classification of the various masking techniques adopted by Welles.